MORAL PERSPECTIVES IN THE WORKS OF CHILDREN'S AUTHOR MICHAEL MORPURGO (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes morals, value and social issues in the works of the famous English children's writer Michael Morpurgo. Through the bright images in almost all of his works, the reader illuminates the social and moral issues of the relationship between parents and children, moral values, dignity, love and care for mother nature, as always, with delicacy and skill.